2023
DOI: 10.17343/sdutfd.1159213
|View full text |Cite
|
Sign up to set email alerts
|

Akri̇lami̇de Maruz Kalan Siçanlarin Kalp Dokusu Üzeri̇nde Selenyumun Koruyucu Rolü

Abstract: Objective: Acrylamide (ACR) is a harmful organic reactive compound widely used in different industrial fields. Selenium (SEL) is a trace element that takes part in some chemical and enzymatic reactions in both animals and human organisms and can cause some disorders in many systems such as the cardiovascular system in case of deficiency. The aim of this study is to investigate whether SEL has a protective effect on cardiac tissue in experimentally induced ACR toxicity in rats. Material and Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…every 72h for 21 days and left without any treatment for 30 and 60 days as compared to NC group. Similar findings were achieved by [2,28,29,27]. The increase in cystolic LDH activity by PARA may be because of the intracellular collection of Ca 2+ , which results in initiation of phosphofructo-kinase and anaerobic glycolysis prompting lactate formation [29].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…every 72h for 21 days and left without any treatment for 30 and 60 days as compared to NC group. Similar findings were achieved by [2,28,29,27]. The increase in cystolic LDH activity by PARA may be because of the intracellular collection of Ca 2+ , which results in initiation of phosphofructo-kinase and anaerobic glycolysis prompting lactate formation [29].…”
Section: Discussionsupporting
confidence: 71%
“…PARA passes through many organs through the circulatory system and causes toxic effects by reacting with DNA and various enzymes [27]. The results in this work showed that PARA caused a highly significant increase (P < 0.05) found in CK-MB and LDH levels in treated rats that given PARA at a dose of (750 mg/kg b.w.)…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation